Improving Employment and Earnings in 21st Century Labor Markets: An Introduction - Erica L. Groshen; Harry J. Holzer (Institute of Labor Economics (IZA), 2019)
What are the prospects for improving the lot of US workers in the 21st century? This introduction to the topic examines the most important US labor market trends of the late 20th and early 21st centuries, considers their causes and likely future trends; and then explores policies that might improve these outcomes. The most important broad labor market trends in recent decades have been: 1) Modest real wage growth; 2) Rising earnings inequality; and 3) Declining labor force participation, recently among both men and women, but especially among less-educated or African-American men and low-income youth over several decades. Key causes of these trends include labor demand and supply factors (such as automation, immigration, and limited college attainment); changing labor market institutions (such as declining unionism and stagnant federal wage/hours laws); rising alternative staffing arrangements, informal work and "fissuring"; and uneven labor market progress and policies affecting women, African-Americans and the young. After that review, we summarize what the papers in our volume tell us about the public policies that could help improve outcomes for US workers. The main message is that further deterioration in many US workers' lives in the 21st century likely requires public and employer policy changes to help to translate the forces at work into better outcomes for them.
Keywords: J01; J08; J2; J5; 330; employment; earnings; inequality; labor force